(untitled) (Voice: A Biannual & Bilingual Journal, 2023)
This paper aims to investigate the reading habits and attitudes of students in the Faculty of Management, Mahendra Multiple Campus, Nepalgunj. The importance of reading as a means to intellectual and emotional growth is discussed, emphasizing the advantages that reading can bring. To collect the necessary data, a questionnaire was designed and distributed to 80 students, probing into their reading habits, preferences, and attitudes. Through quantitative analysis of the findings, it was revealed that the students held an overall positive attitude towards academic and leisure reading, reading either daily or at least once a week. Additionally, digital materials were preferred to printed texts due to their availability and convenience. Based on these results, recommendations were made to improve the reading habits and attitudes of students, including the necessity of a national survey on Nepali students’ reading habits. Finally, the importance of teachers in motivating students to read was highlighted, as the study showed that they can significantly impact students’ reading habits and attitudes.